Estética y política de la identidad - Agier, Michel (Sociedad y Economía, 2008)
Paying attention to the carnivals of three places in the world (Tumaco in Colombia, Salvador Bahia in Brazil and London's Notting Hill), this text elaborates on a nonessentialist notion of "social and cultural identities" and shows the way such identities are articulated with processes of social mobility and groups requirements.